The relationship between property rights and economic growth: An analysis of OECD and EU countries - Ceyhun Haydaroglu (DANUBE: Law, Economics and Social Issues Review, 2015)
In recent years, institutions and institutional structure have become some of the most popular concepts analyzed by economics theory. New growth theories have especially focused on the effects of institutions and institutional structure on a macro level. Property rights are one of the most important elements of this institutional structure. The relationship between property rights and economic growth have drawn the attention of many researchers and policymakers in recent years. The aim of this study, covering the period 2007-2014, is to examine the relationship between property rights and economic growth with the help of PARDL in OECD and EU countries. According to the result of a bounds test, there is cointegration between the variables. The long- and short-term relationships between series were determined and the results taken from the analysis show that there is a positive effect on economic growth in those countries.
Keywords: 330; Property Rights; Economic Growth; EU; OECD; ARDL Bounds Test Analysis